The Efficacy of Antioxidant Oral Supplements on the Progression of COVID-19 in Non-Critically Ill Patients: A Randomized Controlled Trial - Mahmoud M. A. Abulmeaty; Ghadeer S. Aljuraiban; Sumaya M. Shaikh; Naif E. ALEid; Lulwa R. Al Mazrou; Abdullah A. Turjoman; Mona S. Aldosari; Suhail Razak; Mervat M. El-Sayed; Tahani M. Areabi; Rokia M. Alsalafi; Yasser S. Al-Helio; et al. (MDPI AG, 2021)
Modulation of cytokine production using immunonutrition is a relatively novel concept to improve outcomes among patients with SARS-CoV-2 infection and is now hypothesized to help manage COVID-19, however, clinical evidence is lacking. This prospective, double-blinded, randomized parallel-controlled interventional clinical trial investigated the effect of antioxidant supplements on inflammatory cytokines and disease progression in non-critically ill patients. A total of 87 hospitalized COVID-19 patients were randomized using computer-generated-randomization into the supplement group (n = 18) and the placebo group (n = 16) for 10 days. Baseline and final nutritional screening via nutrition risk screening (NRS-2002) and subjective global assessment (SGA), as well as the recording of anthropometric, clinical, biochemical, and functional parameters, were done. Serum ferritin level, cytokine storm parameters such as interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), monocyte chemoattractant protein 1(MCP-1), C-reactive protein, total leukocyte count, lymphocytic count, and neutrophil-to-lymphocyte ratio were measured. Anthropometric and clinical parameters showed nonsignificant differences between groups. The hematology profile showed improvement in lymphocyte count in the supplement group. However, levels of alkaline phosphatase, IL-6, TNF-α, and MCP-1 were significantly lower in the supplement group. In conclusion, antioxidant oral supplementation significantly reduced the cytokine storm and led to partial improvements in clinical parameters among patients with non-critical COVID-19.